STEREOTIP TERHADAP MASYARAKAT BETAWI DALAM NOVEL SI DUL ANAK JAKARTA DAN FILM SI DOEL ANAK BETAWI - Rera Sarah; Rizky Haryanti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to compare the stereotypes of Betawi people in the novel Si Dul Anak Jakarta and the film Si Doel Anak Betawi using ecranization studies. The adaptation of the novel to the film occurred because the novel was already well-known or popular among the public, one of which was the novel Si Dul Anak Jakarta which was made into the film Si Doel Anak Betawi. Si Dul Anak Jakarta succeeded in breaking the stigma of society regarding the image of the Betawi people who are lazy and only have muscle capital. This research uses a descriptive approach with a case study method. The results show that there is a comparison of stereotypes of Betawi people in novels and films. The stereotypes are like the Betawi people who have good social relations and reflect equality, the Betawi people are uneducated, the Betawi people adhere to the devout and fanatical Islamic religion, and the Betawi people only have muscles. Keywords: stereotype, comparative literature, ecranization